PENGGUNAAN METODE PEMBELAJARAN EKSPERIMEN UNTUK MENINGKATKAN PEMAHAMAN SIFAT KOLIGATIF LARUTAN - VINA N VAN HARLING (SOSCIED, 2022)
This researchis carried out aimed at seeing the improvement of students' abilities in the material of colligative properties of solutions using problem-based learning models using experimental methods. This methodis used to find the influence of the use of problem-based learning models on students' understanding of the colligative nature of solutions. This research was conducted in class XII IPA 1, with the research design used was a design that only used one group pretest (one group pretest – posttest design). The variable used in the study is the ability of students to understand the material of the colligative properties of the solution before and after using the problem-based learning model with the experimental method. The data obtained in the study were in the form of scores of student test results on the material of colligative properties of the solution before and after using the experimental method and also data on the results of student interviews. H asil research concluded that the use of problem-based learning models with experimental methods increases the ability of students to understand the colligative nature of solutions, where there is an increase of 67% from the initial result of 22% to 89% after the use of problem-based learning models with experimental methods.